Nusyuz in Husband-Wife Relations: An Islamic Legal Analysis of Husbands' Time Limitations and Family Mediation among Police Officers - Sodiq, Yanwar; Ariyadi; Tanjung, Ardi Akbar; Wahdini, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2026)
The high professional demands on police families often result in limited time spent together by husband and wife, leading to a decline in communication, jealousy, suspicion, and domestic conflict. In such circumstances, nusyuz is often narrowly understood as a wife's disobedience, even though it can be rooted in more complex relational disharmony. This study aims to analyze the problem of nusyuz resulting from husbands' limited time and to examine the practice of family mediation as a conflict resolution mechanism in police families in Gunung Mas Regency, Central Kalimantan. The study used a qualitative method with a normative-empirical legal design dominated by a normative-conceptual approach. Data were obtained through interviews with the marriage registrar and two informants from police families, as well as a review of the Qur'an, hadith, the Compilation of Islamic Law, and Islamic jurisprudence literature. The results indicate that nusyuz is more accurately understood as a symptom of relational disharmony resulting from weakened communication and unmet spiritual needs, rather than solely physical disobedience. Family mediation is the primary choice due to its familial nature and privacy, although it has the potential for bias if not conducted neutrally. The novelty of this research lies in the reinterpretation of the concept of nusyuz as a relational problem and the integration of the perspective of maqashid al-syari'ah in assessing family mediation based on sharia justice.